Effect of fertilizer and successive cutting on growth, yield, phytochemicals, antioxidant and antimicrobial activities of bermuda grass (Cynodon dactylon) - Vella Fung Ah Chon (2017)
Cynodon dactylon (L.) Pers. or commonly known as a Bermuda grass has been reported to have an antioxidant and antimicrobial properties. A series of experiments were conducted to examine the effect of fertilizers (organic A and B; inorganic NPK 15-15-15), fertilizer rates (12.5 or 25 kg N ha-1 per month) and successive cutting (first, second and third) on concentration of phytochemicals (total phenolic, total flavonoid, total saponin and total alkaloid contents) and antioxidant and antimicrobial activities of Bermuda grass. The organic fertilizer A was NPK 8-8-8, trace element, organic matter and humic acid meanwhile, organic fertilizer B was NPK 5-5-5, trace element, organic matter and effective microorganisms. First, second and third successive cutting was carried out repetitively on the same grass at 10, 15 and 20 weeks after planting, respectively. Growth parameter measurements were leaf width (mm), internodes length (cm), shoot density (tillers ha-1), and clipping yield (kg of dry weight ha-1). The results indicated that 25 kg N ha-1 per month of inorganic fertilizer increased grass shoot density significantly. Clipping yield was the highest at first successive cutting and 25 kg N ha-1 fertilizer application per month. The growth assessment supported the rationale for frequent mowing in turf grass management that it's improves new tiller production and reduces grass internode length and leaf width. For the phytochemical analysis, the addition of organic fertilizer B at 12.5 kg N ha-1 per month enhanced total flavonoid and antioxidant activity evaluated as lower IC 50 value and higher ferric reducing ability. There was a positive correlation between total phenolic and flavonoid content with antioxidant activity of the grass extract indicating medicinal value of the grass. With reference to harvest time, successive cutting was found to have reduced significantly the grass clipping yield. However, at either 12.5 or 25 kg N ha-1 application per month of inorganic fertilizer successive cutting was found to have increased the antimicrobial activity and phytochemical concentration of the grass. Successive cutting also found beneficial to improve antioxidant activity as it increased in number. In respect to antimicrobial activity, the grass extract showed a broad spectrum activity on the tested pathogens. Grampositive rather than gram-negative bacteria were found to be susceptible to the antimicrobial activity of the grass extract. The MIC values were ranging 6.25 to 25 mg mI-1 for Bacillus cereus while 12.5 to SO mg mI-1 for Staphylococcus aureus and Salmonella typhi. The MBC value was < 200 mg mI-1 for B. cereus, 50 to 200 mg ml- 1 for S. aureus and 100 to 200 mg mI-1 for 5. typhi. A positive correlation between total saponin content and antimicrobial